رۆژهەڵاتى ناوەراست لە ئەگەرى دووبارەبوونەوەى سایکس - پیکۆیەکى نوێدا - ئه‌حمه‌د, چنور جه‌عفه‌ر (Sulaimani Journal for Humanities, 2018)
ABSTCRAT Sykes-Picot Agreement of 1916 (the Agreement) is a bilateral agreement entered into between two allied states of the World War I against the Ottoman Empire, which led to the creation of Arab, Turkish and Persian states, and defined their boundaries. In the centre of these newly created states, Kurdistan was partitioned and was distributed among them. In this research, the researcher reveals and analysis those secrete letters exchanged between the two allied states, namely; British Empire and France upon depending on the primary documents available at the National Archive at Kew. In nearly one century after this agreement, the Middle East entered a wide scale of revolution called Arab Spring that dramatically skirmished the entire region. This new phase of the region gives rise to the question whether Kurds can take advantages of this event in order to establish their own independent state. The question stems from a consideration to the newly formed Western Kurdistan cantons, and the increasingly worrying level of peace and security crises in the Northern Kurdistan. The aim of the research is to contribute to the literature of the political history of the Middle East through examining how these two allied states were perceiving about the Kurdish nation during the World War I. Next, to examine whether the Agreement created conflicts between the regional powers like Turkish nationalists and the Ottomans and even Persians in one hand, while the allied two states including Russians in the other hand. Upon the implementation of all the critical analysis to the relevant factors of the research topic, the researcher will focus on the American roles in the region, their new project on creating a new Middle East political structure in light with the role of Kurdish Peshmerga and oil resources of the Kurdistan Regional Government. Finally, the researcher will recommend the Kurdish leaders and elites on what necessary steps to be taken while going through this historical opportunity.